Systemic immune-inflammatory markers and long-term prognosis after revascularization in Moyamoya disease: a retrospective study - Wang, Shuang; Liu, Wei; Zhai, Yuanren; Liu, Chenglong; Ge, Peicong; Zhang, Dong (Frontiers in Neurology, 2024)
Background Systemic immune-inflammatory markers combine various individual inflammatory cell parameters to comprehensively explore their relationship with the development and long-term outcomes of cardiovascular, cerebrovascular, and oncological disorders. The systemic immune-inflammatory marker index has not been extensively studied in terms of its impact on the long-term prognosis following cerebral revascularization in MMD patients. Our research aims to address this gap and improve the prediction of long-term outcomes for these patients. Methods We included 851 patients with Moyamoya disease who underwent cerebral revascularization at our medical center from 2009 to 2021. Systemic immune-inflammatory markers were calculated based on routine blood test results at admission, and follow-up was conducted for over 6 months after surgery. During monitoring and upon release, we evaluated patient neurological condition by utilizing the modified Rankin Scale (mRS). We examined the correlation between alterations in mRS ratings and systemic immune-inflammatory markers. Results Comparing the unfavorable long-term prognosis group to the favorable long-term prognosis group, it was found that the NLR level was markedly higher (p = 0.037), while the LMR was lower in the unfavorable long-term prognosis group (p = 0.004). Results from logistic regression analysis revealed that the high-level LMR group had a lower risk of unfavorable long-term prognosis compared to the low-level group (T3: OR = 0.433, 95% CI [0.204–0.859], p = 0.026). The AUC of the model was 0.750 (95% CI [0.693–0.806]). Conclusion Lymphocyte-to-monocyte ratio levels are independently linked to an increased risk of unfavorable long-term prognosis, highlighting LMR as a new and effective predictor for postoperative Moyamoya patients.